Perfusion for congenital heart surgery : notes on cardiopulmonary bypass in a complex patient population - Matte, Gregory S. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2015)
-Confidently devise a safe and successful'plan for the pump run' for patients undergoing surgery for congenital heart disease. This practical guide for perfusionists and other members of the cardiac surgical team provides information on the devices, technology and techniques required for successful bypass of patients with congenital heart defects -A practical, spiral-bound, go-to reference designed to answer the most frequently-posed questions about bypass for CHD, the surgical treatment of which is often complicated -Focuses on the latest technology and techniques and provides clear, matter-of-fact guidance based on specific diagnoses -Written by a seasoned perfusionist who is co-chief and educator at one of the world's leading children's hospitals -Spiral binding allows the book to be laid flat for easy referral in the operating room -A notes section following each diagnosis enables readers to add institution and/or surgeon-specific information to tailor a bypass plan for each CHD lesion.
Equipment for bypass -- Priming the bypass circuit -- The bypass plan -- Typical phases of cardiopulmonary bypass -- Additional notes based on bypass tasks -- Bypass considerations based on diagnosis -- Notes on select issues during bypass -- Notes on select emergency procedures during bypass -- Brief overview of named procedures and terms -- Abbreviations for congenital heart surgery.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Heart Defects, Congenital -- surgery; Infant; Cardiopulmonary Bypass -- instrumentation; Cardiopulmonary Bypass -- methods; Child; Perfusion -- Methods; Congenital heart disease -- surgery; MEDICAL / Surgery / General; Congenital heart disease -- Surgery; Medical; Electronic books; Electronic books; Electronic books